2023
DOI: 10.1002/hsr2.1056
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term mortality and cardiovascular events of seven angiotensin receptor blockers in hypertensive patients: Analysis of a national real‐world database: A retrospective cohort study

Abstract: Background and Aims Although many angiotensin receptor blockers (ARBs) are widely used, comparative data regarding their impact on clinical outcomes are limited. We aimed to compare the clinical effectiveness of seven ARBs on long‐term cardiovascular outcomes in Korean patients with hypertension. Methods Using the Korean National Health Insurance Service database, the data of 780,785 patients with hypertension without cardiovascular disease (CVD) who initiated ARB treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
(104 reference statements)
0
3
1
Order By: Relevance
“…[7] A recently published observational study has shown no difference in the risk of non-fatal MI and stroke among the use of 7 ARBs in patients with hypertension and without cardiovascular disease. [19] However, in our study, differences in the risks of MI and cerebrovascular disease among the use of ARBs were observed using telmisartan use as the reference standard. Valsartan and losartan use were associated with a higher risk of MI but a lower risk of cerebrovascular disease than telmisartan use.…”
Section: Discussioncontrasting
confidence: 62%
“…[7] A recently published observational study has shown no difference in the risk of non-fatal MI and stroke among the use of 7 ARBs in patients with hypertension and without cardiovascular disease. [19] However, in our study, differences in the risks of MI and cerebrovascular disease among the use of ARBs were observed using telmisartan use as the reference standard. Valsartan and losartan use were associated with a higher risk of MI but a lower risk of cerebrovascular disease than telmisartan use.…”
Section: Discussioncontrasting
confidence: 62%
“…A previous meta-analysis of randomized clinical trials has shown no difference in the risk of MI and stroke among the use of the studied ARBs [7]. A recently published observational study has shown no difference in the risk of non-fatal MI and stroke among the use of seven ARBs in patients with hypertension and without cardiovascular disease [20]. However, in our study, differences in the risks of MI and cerebrovascular disease among the use of ARBs, using telmisartan use as the reference standard, were observed.…”
Section: Discussionmentioning
confidence: 96%
“…The Renin-angiotensin-aldosterone system (RAAS) plays a crucial role in the pathogenesis of hypertension, prompting the latest guidelines to recommend angiotensin II receptor blockers (ARBs) as first-line therapy ( 21 , 22 ). By inhibiting Ang II binding to the angiotensin II type 1 receptor (AT1R), ARBs effectively mitigate vascular resistance, reduce blood pressure, and impede RAAS activation, thereby protecting target organs and preventing cardiovascular endpoint events ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%